34. CHARACTERISTICS OF SEPTOPLASTY PATIENTS AT LE VAN THINH HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: This study aims to describe the characteristics of septoplasty patients fixed by the trans-mucosal suture method at Le Van Thinh Hospital.Methods: A descriptive cross-sectional study on patients diagnosed with deviated septum undergoing septoplasty by trans-mucosal suture at Le Van Thinh Hospital from September 2022 to June 2023.Results: A total of 41 cases were included in the study with an average age of 36.9 ± 12.5 years, predominantly male (53.7%), and occupation mainly office workers (36.7%). The duration of illness ranged from 1-3 years (73.2%). Results recorded that 100% of patients were admitted with symptoms of nasal congestion, runny nose, sneezing (75.6%), headache (58.5%), and reduced sense of smell (7.3%). Most patients had severe nasal congestion (63.4%), moderate (31.7%), and very severe (4.9%). The average NOSE score evaluating preoperative nasal congestion was 60.37 ± 11.42.Conclusion: The study provides evidence on the clinical characteristics of septoplasty patients at the hospital, which can help in selecting appropriate interventions for patients.
Keywords: Septoplasty, NOSE score, Le Van Thinh Hospital